A Flexible Pulse Generator Based on a Field Programmable Gate Array Architecture for Functional Electrical Stimulation - Mercado-Gutierrez, Jorge A.; Dominguez, Ricardo; Hernandez-Popo, Ignacio; Quinzaños-Fresnedo, Jimena; Vera-Hernandez, Arturo; Leija-Salas, Lorenzo; Gutierrez-Martinez, Josefina (Frontiers in Neuroscience, 2022)
Non-invasive Functional Electrical Stimulation (FES) is a technique applied for motor rehabilitation of patients with central nervous system injury. This technique requires programmable multichannel systems to configure the stimulation parameters (amplitude, frequency, and pulse width). Most FES systems are based on microcontrollers with fixed architectures; this limits the control of parameters and the scaling to multiple channels. Although field programmable gate arrays (FPGA) have been used in FES systems as alternative to microcontrollers, most of them focus on signal acquisition, processing, or communication functions, or are for invasive stimulation. A few FES systems report the use of FPGAs for parameter configuration and pulse generation in non-invasive FES. However, generally they limit the value of the frequency or amplitude parameters to enable multichannel operation. This restricts the free selection of parameters and the implementation of complex modulation patterns, previously reported to delay FES-induced muscle fatigue. To overcome those limitations, this paper presents a proof-of-concept (technology readiness level three-TRL 3) regarding the technical feasibility and potential use of an FPGA-based pulse generator for non-invasive FES applications (PG-nFES). The main aims of this work are: 1) the development of a flexible pulse generator prototype for FES applications and 2) to perform the proof-of-concept of the system, comprising: electrical test bench characterization of the stimulation parameters, and verification of the potential use of the prototype for upper limb FES applications. Biphasic pulses with high linearity (r2 >0.9998) and repeatability (>0.81) were achieved by combining the PG-nFES with a current-controlled output stage. The average percentage error was under 3% for amplitude (1-48 mA) and pulse width (20-400 μs), and null (0%) for frequency (10-150 46 Hz). A six-channel version of the PG-nFES was implemented to demonstrate the scalability feature. The independence of parameters was tested with three patterns of co-modulation of two parameters. Two complete FES channels were implemented and the claimed features of the PG-nFES were verified by performing upper limb functional movements involving one and two muscles/joints. Finally, the system enabled implementation of a stimulation pattern with co-modulation of frequency and pulse-width, applied successfully for elbow flexion with advantages in range of motion.